Pupillary transient responses to within-task cognitive load variation. (December 2016) - Wong, Hoe Kin; Epps, Julien
Highlights: Pupillary responses to instantaneous changes of cognitive load were characterised. Increasing within-task rate of cognitive loading increases rate of pupil dilation. Pupil size can measure within-task changes of cognitive load consistently. Abstract: Changes in physiological signals due to task evoked cognitive load have been reported extensively. However, pupil size based approaches for estimating cognitive load on a moment-to-moment basis are not as well understood as estimating cognitive load on a task-to-task basis, despite the appeal these approaches have for continuous load estimation. In particular, the pupillary transient response to instantaneous changes in induced load has not been experimentally quantified, and the within-task changes in pupil dilation have not been investigated in a manner that allows their consistency to be quantified with a view to biomedical system design. In this paper, a variation of the digit span task is developed which reliably induces rapid changes of cognitive load to generate task-evoked pupillary responses (TEPRs) associated with large, within-task load changes. Linear modelling and one-way ANOVA reveals that increasing the rate of cognitive loading, while keeping task demands constant, results in a steeper pupillary response. Instantaneous drops in cognitive load are shown to produce statistically significantly different transient pupillary responses relative to sustained load, and when characterised using an exponential decay response, the task-evoked pupillary response time constant is in the order of 1–5 s. Within-task test–retest analysis confirms the reliability of the moment-to-moment measurements. Based on these results, estimates of pupil diameter can be employed with considerably more confidence in moment-to-moment cognitive load estimation systems.